Geographical dispersion and environmental impact assessment of wind power generation in Turkey - Yumurtaci, Zehra; Demirhan, Yasin (INDERSCIENCE ENTERPRISES LTD, 2018)
In the current study, different temporal electricity generation cases of wind farms are examined. The maximum and minimum power generation and capacity factor variations for various regions are calculated based on the actual data taken from the available wind power plants. Also, the amounts of CO2 emission prevention, due to the established wind power plants in these regions, and the related environmental impacts are studied in detail. Furthermore, three distinct regions are taken into account for study, and its results show that the total wind power generation for available 34 wind power plants can go up to 1.2 GW/year in each region. By employing wind power plants in each region, significant reductions of CO2 emissions are possible compared to the conventional coal based power generation. For example, the reductions of CO2 emissions are estimated to be 47,700, 770,000 and 1,032,000 tonnes/year, respectively for three regions of Mediterranean, Marmara and Aegean regions.
Keywords: wind power; environmental impact; CO2 emissions; geographical dispersion; Turkey; ENERGY; Environmental Sciences & Ecology